Edible marijuana products and potential risks for pediatric populations. Issue 3 (June 2022) - Lin, Allison; O'Connor, Mary; Behnam, Reta; Hatef, Claudia; Milanaik, Ruth
Abstract : Purpose of review: In recent years, an increasing number of states have legalized marijuana, also known as cannabis, for recreational use. As marijuana becomes more accessible, adolescent use and accidental pediatric exposures are likely to become broad public health concerns. Edible marijuana products, which are consumable foods or beverages that contain cannabis extract, are particularly enticing to youth, as they come in appealing forms such as candies, cookies, and drinks. The purpose of this review is to provide pediatricians with an overview of the different types and potential dangers associated with edible marijuana products. Recent findings: Edible marijuana products are often indistinguishable in appearance from normal food items and lack the smell and visible smoke associated with inhaled marijuana. Because they are inconspicuous, palatable, and easily accessible, they are increasingly popular among adolescents. Additionally, the packaging of edible baked goods, candies, and drinks is often purposefully very similar to that of mainstream foods, increasing the risk of accidental ingestion by children. An edible marijuana product must be digested before Δ 9 -tetrahydrocannabinol can enter the bloodstream, so there is a delayed onset of effects when consuming edibles compared with inhaling marijuana. This also predisposes users to accidental overconsumption. Summary: Greater knowledge of edible marijuana product consumption by pediatric populations will allow pediatricians to more effectively help patients and advise caregivers in cases of overconsumption, dependence, or accidental ingestion. It is important for parents, guardians, and educators to be able to successfully identify edible marijuana products and recognize signs of cannabis use.